A Critical Analysis on Patriarchy Discussions in Feminist Theory - Güneş, Fatime (Fırat University, 2017)
Feminism is a theoretical approach and a political movement of women's struggle for liberation that analyzes women’s subordination, inequity and oppression experiences in social life and reveals why women are oppressed. As a critical approach, feminism discusses the causes of women's oppression and the processes of liberation, while at the same time criticizing all structures and relationships that have permeated societal life from everyday life to macro processes. One of the most important discussions in feminism both at the theoretical and political level is the issue of patriarchy. As an important tool of oppression over women, patriarchy has always maintained its importance vis-à-vis social theory, in terms of what constitutes it, how to define it, how to explain it, its place in feminist politics, its inclusiveness, and its limitations. The main purpose of this article is to critically define what patriarchy means and how it is conceptualized in terms of different liberal, radical ve socialist feminist theories.

Feminizm kadınların toplumsal yaşamdaki ikincil, eşitsiz ve ezilme deneyimlerini inceleyen, neden ezildiklerini ortaya koyan kuramsal bir yaklaşım ve kadınların özgürleşme mücadelesinin politik bir hareketidir. Eleştirel bir yaklaşım olarak feminizm, kadınların ezilmişliğinin nedenlerini ve özgürleşme süreçlerini tartışırken aynı zamanda günlük yaşamdan makro süreçlere kadar toplumsal yaşama nüfus etmiş bütün yapı ve ilişkileri de eleştiriye tabi tutmaktadır. Feminizm içinde hem kuramsal hem de politik düzeyde yapılan en önemli tartışmalardan biri ataerki meselesidir. Kadınlar üzerinde tahakküm kurmanın önemli bir aracı olan ataerkinin ne olduğu, nasıl tanımlanacağı, nasıl açıklanacağı, feminist siyasetteki yeri, kapsayıcılığı, sınırlılıkları gibi meseleler toplumsal teori açısından önemini hep korumuştur. Bu makalenin temel amacı, ataerkilliğin liberal, radikal ve sosyalist feminist kuramlar açısından ne anlama geldiğini, ataerkilliğin nasıl kavramsallaştırıldığı eleştirel bir şekilde ortaya koymaktır.
FEMİNİST KURAMDA ATAERKİ TARTIŞMALARI ÜZERİNE ELEŞTİREL BİR İNCELEME